The Impact of Financial Inclusion on Financial Stability: Evidence from MENA and African Countries Analyzed Using Hierarchical Multiple Regression - Fadoua Joudar; Omar El Ghmari (Economies)
The link between financial inclusion and financial stability is a central concern in public economic policymaking, particularly in emerging countries where access to financial services remains limited. While financial inclusion is widely regarded as a key driver of economic development, its impact on financial stability remains debated. Some studies highlight the stabilizing effect of financial inclusion, whereas others, like emphasize its potential risks. This study empirically investigates the relationship between financial inclusion and financial stability across the years 2011, 2014, 2017, and 2021 in 26 African and MENA countries. The hierarchical multiple regression (HMR) method is employed to assess the independent effect of financial inclusion, controlling for macroeconomic variables. The findings reveal that financial inclusion positively contributes to financial stability through channels such as digital payments and the number of bank branches. Conversely, savings, the number of ATMs, and the money supply exhibit a negative effect on financial stability. These results underscore the need for a regulatory framework that balances financial inclusion with financial stability. In particular, cybersecurity measures must be implemented to support the expansion of digital payments, and supervisory mechanisms should be reinforced to mitigate liquidity risks.